Perlindungan Konsumen Dalam Perbankan Syariah: Perspektif Hukum Ekonomi Syariah - Faris, Naufal; Winario, Mohd (EL-EMIR Institute, 2024)
This research aims to investigate consumer protection in the context of Islamic banking, with a focus on the legal perspective and best practices implemented. The research method used is descriptive analysis involving literature study and document review to explore various aspects relevant to this topic. The main objectives of this research are to: Examine the various challenges faced in maintaining consumer protection in sharia banking, including clarity of information, sharia compliance, and dispute resolution, investigate best practices that have been implemented by sharia financial institutions in ensuring consumer protection, such as compliance mechanisms strict sharia, conflict management, and consumer education, and provide recommendations for further improvement and development in the consumer protection framework in Islamic banking, both from a legal perspective and operational practices. The results of this research reveal that consumer protection in sharia banking requires a holistic approach that integrates sharia values ​​with best practices in the global financial industry. It is hoped that these findings can provide valuable guidance to regulators, Islamic banking practitioners, and academics in their efforts to strengthen consumer protection frameworks that are effective and in line with Islamic ethical values.